The Influence Of Promotion, Service Quality And Trust On Go Food Customer Satisfaction In Bandar Lampung City - Ardansyah Ardansyah; Shilvia Seprianty (Cita konsultindo, 2024)
This research aims to understand and analyze the influence of promotions, service quality and trust on Go Food customer satisfaction in Bandar Lampung City. The population in this research is Go Food consumers in Bandar Lampung City. The population in this study is unknown. The formula for calculating samples for an unknown population uses the Lemeshow formula. So if based on this formula, the n obtained is 96.04 = 100 people, so in this study the author must at least take data from a sample of at least 100. This analysis uses calculations through statistical methods and to simplify data analysis, this research uses SPSS 25 software. The analysis that will be taken is the multiple linear test, t test, F test, and coefficient of determination test. Based on the results of data analysis, it can be concluded that promotion, service quality and trust have a positive and significant influence together on Go Food customer satisfaction in Bandar Lampung City.